Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1989
DOI: 10.1037/0735-7036.103.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Social influences on the acquisition of tool-using behaviors in tufted capuchin monkeys (Cebus apella).

Abstract: To identify behaviors related to acquisition of tool-use in tufted capuchins (Cebus apella), we presented two tool-using tasks to two groups, extending findings by Westergaard and Fragaszy (1987) and Visalberghi (in press). Five Ss learned to use the tools in each task. The primary predictor of success was level of interest in the task. Observation of others at the apparatus did not facilitate exploratory behaviors or contact with the tools in the observers. Most animals performed exploratory behaviors more of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
1
6

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(87 citation statements)
references
References 35 publications
3
77
1
6
Order By: Relevance
“…Experiments with monkeys in the same period likewise failed to find evidence of imitation (Adams-Curtis, 1987;Antinucci & Visalberghi, 1986;Fragaszy & Visalberghi, 1989;Visalberghi, 1987;Visalberghi & Trinca, 1989;Westergaard & Fragaszy, 1987;Westergaard & Lindquist, 1987). Visalberghi and Fragaszy (1990), reviewing their own and similar experiments, concluded that there was evidence of social learning only at the level of stimulus enhancement.…”
Section: Experimental Studies Of Social Learning Processesmentioning
confidence: 99%
“…Experiments with monkeys in the same period likewise failed to find evidence of imitation (Adams-Curtis, 1987;Antinucci & Visalberghi, 1986;Fragaszy & Visalberghi, 1989;Visalberghi, 1987;Visalberghi & Trinca, 1989;Westergaard & Fragaszy, 1987;Westergaard & Lindquist, 1987). Visalberghi and Fragaszy (1990), reviewing their own and similar experiments, concluded that there was evidence of social learning only at the level of stimulus enhancement.…”
Section: Experimental Studies Of Social Learning Processesmentioning
confidence: 99%
“…Such novel behaviour patterns include the exploitation of new food sources, entry into unknown spaces, or learning to use novel tools (Itani 1965;Katzir 1982;Fragaszy & Visalberghi 1989;Lee 1991). The key characteristic of innovation is the introduction of a novel behaviour pattern into a population's repertoire.…”
Section:  2000 the Association For The Study Of Animal Behaviourmentioning
confidence: 99%
“…Therefore, this 100-h study failed to corroborate the observation of Bortolini & Bicca-Marques (2007) and to reject the hypothesis that capuchins despite their high cognitive abilities are not capable of making tools (Fragaszy & Visalberghi 1989;Fragaszy et al 2004;Ottoni et al 2005). Due to their small body size, callithrichines are probably subject to high predation pressure; in fact, it may be an important factor shaping their cooperative social systems (Caine, 1993).…”
Section: Discussionmentioning
confidence: 55%